Ingestion of microplastics in the planktonic copepod from the Indonesian throughflow pathways - Manullang, Corry Yanti; Patria, Mufti Petala; Haryono, Agus; Sabiqah Tuan Anuar,; Susanto, Raden Dwi; Abdul, Malik Sudin; Fadli, Muhammad; Wei, Zexun (Penerbit Universiti Kebangsaan Malaysia, 2024)
Zooplankton are vulnerable to microplastics in the waters due to their indiscriminate feeding habits. Zooplankton consumption of microplastics affects microplastic accumulation and transmission in the marine ecosystem. Therefore, it is essential to know the intake and transmission by different group sizes of zooplankton in natural seawater. This study documented for the first time the levels of microplastics found in three sizes of copepods along the Indonesian Throughflow (ITF) pathways. The ingestion rates were 0.028, 0.023 and 0.016 n/ind for group sizes copepod 1000-2000 µm, 500-1000 µm and 200-500 µm, respectively. There was no significant distinction in the microplastics concentrations of the three groups of copepod classes along the ITF pathway (p>0.005). Fiber microplastics were the most dominant in the body of copepods, constituting 87.22% of ingested microplastics. In terms of the chemical composition of the microplastic, a total of 7 polymers were detected in copepods in the ITF pathway. The three predominant polymer types identified were polyvinyl butyral (PVB), polyvinyl ether maleic anhydride (PVEMA) and polyester (PES) (27%, 27% and 20%, respectively). This study provides the critical parameters of the microplastic in copepods in the ITF pathway and is an essential basis for further ecological risk assessments of microplastics in biota species.